GiggleSquid
Need quick help. Picture attatched



This Question is Closed

GiggleSquid
Best Response
You've already chosen the best response.
0

across
Best Response
You've already chosen the best response.
1
Let \(f(x)=\sqrt{9x}\) and \(g(x)=x+7\). Then \((f\circ g)(x)=f(g(x))=f(x+7)=\sqrt{9(x+7)}=3\sqrt{x+7}\).

GiggleSquid
Best Response
You've already chosen the best response.
0
at the f(g(x)) part im confused, how did you get f(x+7)

GiggleSquid
Best Response
You've already chosen the best response.
0
@across